Editorial: Leadership Education – The Start of a Voyage of Discovery - Miller, Paddy (Senate Hall Academic Publishing, 2005)
Leadership probably ranks highly on any short list of organizational priorities. One can hardly find a CEO who is not concerned about developing leadership capability in his or her organization. As a result “leadership” has become one of the most taught subjects in management development programs in recent years. It should thus be a rich area for sharing new ideas, for revealing the secrets of success and what is to be learned from failure. All objectives of this new International Journal of Leadership Education. The challenge for the editors has been to tap those people in leadership education who could bring insight to others about what they know and what they practice out there in the real world. This has not been easy. The number of approaches to educating leaders has proliferated as universities, business schools, consultants and individual presenters, facilitators and coaches adopt widely differing conceptual models. A quick search on Google turns up 51.9 million hits on the word “leadership” and 20.8 million on “leadership education”!